Workplace trauma and professional quality of Life in clinical and forensic psychiatry: the CRITIC study - Bloemendaal, Anthony F. T.; Kamperman, Astrid M.; Bonebakker, Annette E.; Kool, N.; Olff, M.; Mulder, C. L. (Frontiers in Psychiatry, 2024)
Background: Frontline staff in psychiatry need to perform at a very high professional level in order to ensure patient and community safety. At the same time they are exposed to high levels of stress and workplace trauma. This may have severe consequences for their professional quality of life. In addition, health care workers in general have higher incidence levels of childhood adversity than the general population.The CRITIC (CRITical Incidents and aggression in Caregivers) Study aims to improve increased understanding of the interaction between personal life history (childhood adversity and benevolence), individual capabilities, exposure to trauma and violence at work and Professional Quality of Life (ProQOL).The Critic Study is a cross-sectional survey of these aspects in frontline, treatment and administrative staff in clinical and forensic psychiatry. We aim to include 360 participants. Participants will be asked to complete questionnaires on childhood adversity and childhood benevolence (assessing personal life history), professional quality of life, current trauma and violence exposure, current mental health (depression, anxiety and stress), coping, social support, work engagement and resilience. In this study we will examine the moderating role of adverse and benevolent childhood experiences in the association between workplace trauma exposure and professional quality of life. Finally, a theoretical model on the relationships between trauma, stress and coping in the context of professional functioning will be tested using structural equation modelling.Discussion: The CRITIC study examines which factors influence the complex relationship between childhood adversity and benevolence, and ProQOL in healthcare workers. It also aims to provide insight into the complex relationship between personal life history, individual characteristics, exposure to trauma and violence at work and ProQOL. The results can be used for designing interventions to increase resilience to trauma and to improve professional quality of life among health care professionals.The CRITIC study has been approved by the Medical Ethical Committee of the Erasmus Medical Centre, under trial registration number NL73417.078.20